Bravo Chere,Patricia Adaluz(2023)PRODUCCIÓN DE FORRAJE VERDE HIDROGERMINADO DE MAÍZ (Zea mays) CON DIFERENTES PORCENTAJES DE SOLUCIÓN NUTRITIVA DE HOAGLAND.Quevedo.UTEQ.63p. - Bravo Chere , Patricia Adaluz (2023)
This research was carried out on the grounds of the Universidad Técnica Estatal de Quevedo, Campus "La María". Production of hydrogerminated maize (Zea mays L.) green forage with different percentages of Hoagland's nutrient solution. The treatments were: T0: Natural water; T1: 25 % Hoagland Nutrient Solution; T2: 50 % Hoagland Nutrient Solution; T3: Hoagland's Nutrient Solution at 75 % and T4: Hoagland's Nutrient Solution at 100 %. A completely randomized design (DCA) was used. Variables were analyzed using Tukey's test (P<0.05). For agronomic behavior, the variables were plant height (AP), leaf diameter (DH), leaf length (LH), stem diameter (DT), root length (LR). For the bromatological composition: dry matter (DM), organic matter (OM) and neutral detergent fiber (NDF). The nutritive solutions influenced (P<0.05) the agronomic behavior for the AP and LH in the treatments T4 and T3 (20,14 and 19,94 cm) and (14,38 and 14,25 cm) respectively, the LR in the T2 (6,38 cm), the DT in the T1 and T2 (0,31 and 0,31 cm) and in the NH in the T2 and T3 (3,30 and 3,30 cm). For the bromatological composition in the MS in T4 (18,91 %) and for NDF in T4 and T0 (43,51 and 42,24 %) respectively. It is concluded that nutrient solutions have better results in agronomic behavior and bromatological composition. Keywords: Biomass, fertilizer, hydroponics